Assessment of the Relationship between Body Weight Status and Physical Literacy in 8 to 12 Year Old Pakistani School Children: The PAK-IPPL Cross-Sectional Study - Yinghai Liu; Syed Ghufran Hadier; Long Liu; Syed Muhammad Zeeshan Haider Hamdani; Syed Danish Hamdani; Shaista Shireen Danish; Syeda Urooj Fatima; Yanlan Guo (MDPI AG, 2023)
(1) Background: Physical literacy (PL) is a multidimensional concept, since it fosters lifetime engagement in physical activities and reduces obesity; however, empirical evidence is lacking to support this association. This study first aimed to establish PL levels stratified by normal weight children and children with overweight and obesity. Furthermore, this study determined a correlation between PL domains and BMI by weight status among South Punjab school children. (2) Methods: This cross-sectional study involved 1360 (Boys: 675 and Girls: 685) children aged 8 to 12, and was conducted using CAPL-2. T-tests and chi-square were used to determine the difference between categorical variables, with MANOVA used to compare weight statuses. Spearman correlation was employed to determine the correlation between variables; p < 0.05 was considered significant. (3) Results: Normal weight children had significantly higher PL and domain scores, except for the knowledge domain. Most children with normal weights were at the achieving and excelling levels, while children with overweight and obesity were at the beginning and progressing levels. The correlation among PL domains in normal and overweight and obese children ranged from weak to strong (r = 0.001 to 0.737), and the knowledge domain was inversely correlated with the motivation domain (r = −0.023). PL and domain scores were inversely correlated to BMI, except for the knowledge domain. (4) Conclusions: Children with normal weight tend to have higher PL and domain scores, while those with overweight or obesity tend to have lower scores. There was a positive relationship between normal weight and higher PL and domain scores, and an inverse relationship was observed between BMI and higher PL scores.